Monoterpene indole alkaloid hydrazone derivatives with apoptosis inducing activity in human HCT116 colon and HepG2 liver carcinoma cells. Issue 17 (1st September 2015) - Paterna, Angela; Borralho, Pedro M.; Gomes, Sofia E.; Mulhovo, Silva; Rodrigues, Cecília M.P.; Ferreira, Maria-José U.
Graphical abstract